2019
DOI: 10.1038/s41598-019-42195-w
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: The genetic legacy of continental scale admixture in Indian Austroasiatic speakers

Abstract: A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The admixture between local Indians and incoming Southeast Asians took place ~2000-3800 years ago giving rise to the AAA ancestry. Notably, the Indian population(s) with whom the incoming Southeast Asians mingled were AASI related with little to no West Eurasian ancestry fraction [47]. Finally, it has been showed that the Tibeto-Burmans (ATBs) derived their ancestry through admixture with low-altitude East Asians who migrated from China and likely across Northern India or Myanmar [48] leading to the high genomic proximity between Indians of ATB ancestry and East Asians.…”
Section: Discussionmentioning
confidence: 99%
“…The admixture between local Indians and incoming Southeast Asians took place ~2000-3800 years ago giving rise to the AAA ancestry. Notably, the Indian population(s) with whom the incoming Southeast Asians mingled were AASI related with little to no West Eurasian ancestry fraction [47]. Finally, it has been showed that the Tibeto-Burmans (ATBs) derived their ancestry through admixture with low-altitude East Asians who migrated from China and likely across Northern India or Myanmar [48] leading to the high genomic proximity between Indians of ATB ancestry and East Asians.…”
Section: Discussionmentioning
confidence: 99%